Family Development Theory on Childcare Dual Career Families: Systematic Literature Review - Merida Reformasi; Kukuh Septio Aji; Ika Febrian Kristiana (Proceedings of International Conference on Psychological Studies (ICPSYCHE), 2022)
Dual-career family is a family phenomenon in which the father and mother both work outside the home so that the practice of parenting involves internal or external parties (eg grandparents, uncles, neighbors, household assistants, or day care). This study is a systematic literature review that aims to examine dual career family parenting. Online databases used: Scient Direct, Google Scholar, Springer, and Sage Journal with the keyword "childcare" AND "dual career families” OR “dual earner family” OR “dual income family” OR “dual worker family”. Following PRISMA-2015, this study applies inclusion criteria (peer review articles, literature study of quantitative methods, articles on parenting of children with dual career families, parenting of children with stages of childhood development). Total (N= 4 articles) were involved in the review process after going through the screening and selection process. The results of the review show difference in dual career family parenting practices in various countries based on family development theory. The results of this study show that in Finland formal child care is lower than in the Netherlands, and finds that informal parenting is higher in the UK. As for another study in South Korea, it was found that when the baby was a dual career family, they practiced child care in a certain institution. On the other hand, it was found in Spain that the upbringing of dual career family children is through parenting by grandparents. This indicates where a particular family system develops dynamic functions as the family travels and develops. Family development theory becomes a systematic framework for determining the functions of the family unit in accordance with the development that has been passed.